2003
DOI: 10.1002/bem.10148
|View full text |Cite
|
Sign up to set email alerts
|

Radial arm maze performance of rats following repeated low level microwave radiation exposure

Abstract: We examined the possibility of changes in "working" memory of rats following whole body exposure to microwave (MW) radiation. During each of 10 days, we exposed rats within circularly polarized waveguides for 45 min to 2450 MHz fields at whole body SARs of 0.6 W/kg (2 micros pulses, 500 pps), followed by testing in a 12 arm, radial arm maze (RAM). Rats received a preexposure injection of one of three psychoactive compounds or saline, to determine whether a compound would interact with MW exposure to affect per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 46 publications
2
24
2
Order By: Relevance
“…Alterations in opioid neurotransmitter properties were suggested as a plausible explanation. However, these findings could not be replicated by Cassel et al [2004] or Cobb et al [2004].…”
Section: Discussioncontrasting
confidence: 68%
“…Alterations in opioid neurotransmitter properties were suggested as a plausible explanation. However, these findings could not be replicated by Cassel et al [2004] or Cobb et al [2004].…”
Section: Discussioncontrasting
confidence: 68%
“…Similarly, Dubreuil et al [2002Dubreuil et al [ , 2003 found no effects on the performance of rats on several maze tasks (as well as an object recognition task) following exposure to pulsed 900 MHz fields using a head-only system. Finally, two recent attempts to replicate the radial arm maze experiment of Lai et al [1994] did not find any field-dependent effects [Cassel et al, 2004;Cobb et al, 2004]; such exposures were also shown not to affect anxiety levels as assessed using an elevated plus maze [Cosquer et al, 2005]. In addition, unpublished experiments from the authors' laboratory have found that exposure of mice to fields representing GSM, UMTS or TETRA signals have no significant effects on place learning and spatial memory.…”
Section: Effects On Cognition and Learned Behaviourmentioning
confidence: 91%
“…Average EMR frequency on Apis mellifera colonies during the observation period. recent studies have also demonstrated that various tissues, cellular activities, memory, and learning in humans, rats, and mice are not affected when subjected to GSM or GSM-like microwave radiation (Cobb et al, 2004;Dasdag et al, 2003Dasdag et al, , 2004Dasdag et al, , 2008Dubreuil et al, 2002Dubreuil et al, , 2003Forgacs et al, 2006;Joubert et al, 2007;Kumlin et al, 2007;Sienkiewicz et al, 2000;Smith et al, 2007;Thorlin et al, 2006;Tillmann et al, 2007). Nevertheless, these findings should not downplay the potential health hazards involved with the use of cellular phones.…”
Section: Behavioral Observationmentioning
confidence: 97%